Intergenerational educational mobility in Turkey - Aysit Tansel (Turkish Economic Association, 2015)
This paper aims to provide information on intergenerational educational mobility in Turkey over the last century (at least over the last 65 years). This is the first study explicitly on providing the association between parents' and children's education in Turkey over time unlike the previous studies of one point in time. Given the absence of longitudinal data, we make use of a unique data set on educational outcomes based on children recall of parental education. The data used is the result of Adult Education Survey of 2007. Several findings emerge from the analysis. First of all, children's and parents' educational outcomes are correlated. The intergenerational educational coefficient of the mothers is somewhat larger than that of the fathers. The intergenerational educational coefficients of both the mothers and the fathers decrease over the cohorts implying that intergenerational educational mobility increased significantly for the younger generations of children in Turkey. The chances of attaining a university degree for the children increases as fathers' completed schooling level increases. Men's chances of attaining high school or university education are substantially higher than that of women's. The association between parent and child education is stronger when parent educational background is poor. The results imply that the policy makes should focus on children with poor parental educational background and on women.
Keywords: I21; I28; J11; J62; 330; intergenerational mobility; educational transmission; Turkey